"Nobody's ever held the door open and invited women, Black people or disabled people in": confronting discrimination in Marie NDiaye's theater. (1st September 2022) - Delijani, Clare Finburgh
Abstract : With focus on the two plays which, to date, bookend Marie NDiaye's theatrical career— Hilda (1999) and Royan (2020)—this article illustrates how the French author's theater places center-stage the structures that marginalize people owing to their class, gender, sexuality, racialization, or religion. With reference to theorizations of intersectionality elaborated by Simi Cho, Kimberlé Crenshaw, and Leslie McCall in the US, and Reine Prat in France, the article exposes the compound overlapping forms of domination, subordination, and oppression that discriminate against minoritized individuals and groups. The theory and praxis of intersectionality, they argue, do not concern identity politics or subjectivity; nor do they rate or order the oppression of one group ahead of others. Rather, the concept of intersectionality provides a useful means for apprehending how NDiaye's theater shifts emphasis from discriminated people to the discriminatory structures that minoritize, racialize, and marginalize them. While NDiaye's plays often float free from obvious historical, geographical, or social contexts, they critique, the article argues, specific features of history, politics, society, and economics in France. The article reveals how her theater exposes the French nation's republican values of liberté, égalité, fraternité to be at considerable odds with the reality for women, people who do not conform to heteronormativity, racialized people, and other ostracized or relegated categories.